Intravenous Amisulpride Does Not Meaningfully Prolong the QTc Interval at Doses Effective for the Management of Postoperative Nausea and Vomiting - Fox, Gabriel M.; Albayaty, Muna; Walker, Joanna L.; Xue, Hongqi; Darpo, Borje (Anesthesia and analgesia, 2021)
BACKGROUND:Postoperative nausea and vomiting (PONV) are significant issues in surgical patients, and additional treatment options are needed. Dopaminergic antiemetics have been popular for their efficacy, but their use has been limited by safety concerns, especially the potential for torsade de pointes arising from QT interval prolongation. Intravenous (IV) amisulpride, a dopamine D2 and D3 antagonist shown to be effective at preventing and treating PONV at doses of 5 and 10 mg, respectively, has a dose-dependent effect on QT but at 5 mg is not associated with clinically meaningful prolongation of the heart rate-corrected QT (QTc) interval. This study was designed to evaluate the QT effect of a 10-mg dose of amisulpride, alone and when simultaneously coadministered with ondansetron, an antiemetic of a different class, also known to prolong the QT interval. METHODS:In this randomized, double-blind, placebo-controlled, 3-period, crossover study, healthy male and female volunteers 18–65 years of age received IV, in a random sequence(1) amisulpride 10 mg given twice, 2 hours apart; (2) amisulpride 10 mg and ondansetron 4 mg, given simultaneously; and (3) placebo. RESULTS:Thirty subjects were enrolled, and 29 completed all 3 treatment periods. The largest mean placebo-corrected change-from-baseline QT interval corrected for heart rate using Fridericia’s formula (QTcF) (ΔΔQTcF) after the first and second amisulpride dose was 5.2 milliseconds (90% confidence interval [CI], 3.53–6.96 milliseconds) and 8.0 milliseconds (90% CI, 5.49–10.58 milliseconds), respectively. After coadministration of amisulpride and ondansetron, the largest mean ΔΔQTcF was 7.3 milliseconds (90% CI, 5.48–9.16 milliseconds). The slope of the amisulpride concentration–change-from-baseline QTcF (ΔQTcF) relationship was 0.006 ms/ng/mL (90% CI, 0.0020–0.0098). No QTc outliers (absolute QTcF value >480 milliseconds or increase from baseline >30 milliseconds) were seen in any period. CONCLUSIONS:A 10-mg dose of IV amisulpride, given alone or in combination with ondansetron, does not have a clinically significant effect on the QT interval.